Is the water disinfection by-product dichloroacetic acid biosynthesized in the edible mushroom Russula nigricans?. (October 2021) - Lajin, Bassam; Braeuer, Simone; Borovička, Jan; Goessler, Walter
Abstract: We report the first halogen speciation analysis study by high performance liquid chromatography coupled with inductively coupled plasma tandem mass spectrometry (HPLC-ICPMS/MS) in the fruiting bodies of various mushroom species. Non-targeted speciation analysis revealed the occurrence of dichloroacetic acid (DCAA) in the edible mushroom Russula nigricans . Multiple samples of this mushroom (n = 5) collected from different geographic non-industrial regions in two different countries confirmed the consistent presence of this species at a relatively narrow concentration range (23–37 mg kg −1 ), whereas no other chlorinated acetic acid (e.g. chloroacetic acid and trichloroacetic acid) was detected. Neither DCAA nor any other chlorinated acetic acid were detected in any of the other mushroom species investigated in the present study, including seven different mushroom species of the same genus Russula, even though all mushrooms were collected from the same non-industrial geographic regions. Together with the previously reported biological activities of DCAA, these findings collectively suggest biosynthesis of this compound as an explanation for its dominant presence in R. nigricans, and constitute the first example of the dominant natural occurrence of this compound over other chlorinated acetic acids in a living organism. This may warrant a change in our view of the occurrence of dichloroacetic acid in nature, where primarily considered as a pollutant arising from water disinfection. Highlights: Identification of organohalogen natural products by non-targeted Cl speciation with HPLC-ICPMS/MS. The pharmacologically active dichloroacetic acid (DCAA) is naturally occurring in an edible mushroom. The first report of the natural occurrence of DCAA in a terrestrial multi-cellular organism.